Are Skilled Workers More Attracted to Economic Agglomerations? - Rosa Sanchis-Guarner; Enrique Lopez-Bazo (European Regional Science Association (ERSA), 2006)
The New Economic Geographhy (NEG) models explain the formation and the consolidation of economic agglomerations through a self-sustained process in which a trade-off between centripetal and centrifugal forces takes place. The centripetal forces work through two mechanisms: those known as the backward and the forward linkages. The latter mechanism predicts that workers will be attracted towards economic agglomerations by higher real wages due to smaller price indexes in those regions with greater market potential. Recent contributions have tried to assess this assumption simultaneously estimating some of the structural coefficients of the NEG models. Nevertheless, in all these cases, migrants have been considered to be homogenous. Conversely, the basic hypothesis of this paper suggests that the effect of the market potential on the probability of migrating depends on the human capital level of the workers. The introduction of this assumption is consistent with previous empirical evidence that shows that human capital increases the probability of migration of the workers, accentuating the opportunity cost of not migrating. In agreement with the predictions derived from our theoretical model, the results obtained for the inter-provincial migrations in Spain in the two last decades confirm that qualified workers are more sensible to regional differences in market potential.
Keywords: 330